Gender and Citizenship in the Global Age - Amri, Laroussi (Book collections on Project MUSE., 2014)
One of the major issues this book examines is what the African experience and identity have contributed to the debate on citizenship in the era of globalisation. This volume presents case studies of different African contexts, illustrating the gendered aspects of citizenship as experienced by African men and women. Citizenship carries manifold gendered aspects and given the distinct gender roles and responsibilities, globalisation affects citizenship in different way. It further examines new forms of citizenship emerging from the current era dominated by a neoliberal focus. This book is not exclusive in terms of theorisation but its focus on African contexts, with an in-depth analysis taking into consideration local culture and practices and their implications for citizenship, provides a good foundation for further scholarly work on gender and citizenship in Africa.